THE STUDY OF VALUES REFLECTED IN SECONDARY LEVEL ENGLISH SYLLABUS OF W.B.B.S.E. - Sing, Pradipaditya (International Journal of Research -GRANTHAALAYAH, 2020)
Traditionally in Indian education system values and value education is an integral part which is lacking among the today’s young generations. The objectives of this study are to find out how the English syllabus is helping the students inculcating values, to identify the types of values incorporated in English syllabus of W.B.B.S.E. For this study qualitative method has been undertaken and content analysis has been done. The major findings of this study are that prose lessons are mostly able to develop values among the students than nonfiction and poetry; Nonfiction, though it is little in number of lessons, has high efficiency in the development of values, the English syllabus of W.B.B.S.E is able to develop social values, moral values and national values.